Diagnosing solubility limitations - the example of hydrate formation - Joerg Berghausen; Bernard Faller (International Association of Physical Chemists (IAPC), 2014)
Solubility is regarded as one of the key challenges in many drug discovery projects. Thus, it's essential to support the lead finding and optimization efforts by appropriate solubility data. In silico solubility prediction remains challenging and therefore a screening assay is used as a first filter, followed by selected follow-up assays to reveal what causes the low solubility of a specific compound or chemotype. Results from diagnosing the underlying reason for solubility limitation are discussed. As lipophilicity and crystal lattice forces are regarded as main contributors to limiting solubility, changes in solid state are important to be recognized. Solubility limitation by various factors will be presented and the impact of the solid-state is exemplified by compounds that are able to form hydrates.